Analisis Minat Konsumen terhadap Aplikasi E-Wallet dalam Bertransaksi Dengan Menggunakan Kerangka Technology Acceptance Model - Zaenul Ma'ruf; Adhimas Wisnuyudo; Agrian Dwi Lesmana; Samsudin Samsudin (J-MAS (Jurnal Manajemen dan Sains), 2022)
This study aims to determine the factors that influence the interest in using e-wallet by adopting the Technology Acceptance Model (TAM). The independent variables in this study were Perceived Benefits (X1), Perceptions of Ease (X2) and Security (Y), while the dependent variable was Interest in Use (Y). The population in this study were all e-wallet users in Dago, Bandung with a sample of 190 based on purposive sampling. This research uses multiple linear regression analysis tool with the help of SPSS software for Windows V26. The results of this study indicate that Perception of Benefits (X1) has a positive and significant effect on Purchase Intention (Y), Perception of Ease (X2) has a positive and significant effect on Intention to Use (Y) and Security (X3) has a positive and significant effect on Intention to Use.